The Relationship Between Digital Well-Being Awareness and Students’ Learning Consistency in The Era of Mobile Learning at SMAN 1 Lambitu - Syarif Hidayah; Ady Irawan; Ahyar (UNDIKMA, 2026)
The integration of mobile learning creates a paradox between the effectiveness of accessing learning materials and the risk of digital distractions that threaten students’ learning consistency. This quantitative correlational study aims to describe the levels of digital well-being awareness and students’ learning consistency, as well as to analyse the relationship between these two variables at SMAN 1 Lambitu. The research sample comprised 70 students selected using proportionate stratified random sampling. Primary data were collected via a four-point Likert scale questionnaire and a Research Data Validation Observation Sheet as a triangulation instrument. Statistical analysis included tests of classical assumptions, Pearson’s product-moment correlation, the coefficient of determination (R²), and simple linear regression. The results of the descriptive analysis showed that students’ digital well-being awareness (81%) and consistency in learning (83%) tended to fall within the high category. Hypothesis testing confirmed the existence of a positive and significant correlation of moderate strength between the two variables (r = 0.469; tcalculated= 4.376 > ttable= 1.995; Sig. = 0.000 < 0.05). The R² value of 0.220 indicates that this awareness contributes 22% to learning consistency, as per the regression model Y = 26.131 + 0.487. These findings confirm that metacognitive awareness of device management serves as an essential anchor for the stability of students’ focus and the sustainability of their learning routines.